Conservation characteristics of corn ears and stover ensiled with the addition of Lactobacillus plantarum MTD-1, Lactobacillus plantarum 30114, or Lactobacillus buchneri 11A44 - Lynch, J.P.; O’Kiely, P.; Waters, S.M.; Doyle, E.M. (Journal of dairy science, 2012)
The aim of this study was to investigate the effects of inoculating 3 contrasting lactic acid bacteria on the fermentation profile, estimated nutritive value, and aerobic stability of corn ears and stover produced under marginal growing conditions. Ears and stover were separated from whole-crop corn plants obtained from 3 replicate field blocks. Representative subsamples were precision chopped and allocated to 1 of the following treatments: an uninoculated control, Lactobacillus plantarum MTD-1 (LP1), L. plantarum 30114 (LP2), or Lactobacillus buchneri 11A44 (LB). Each bacterial additive was applied at a rate of 1 × 106 cfu/g of fresh herbage. Triplicate samples of each treatment were ensiled in laboratory silos at 15°C for 3, 10, 35, or 130 d. No difference was observed between the dry matter recoveries of uninoculated ear or stover silages and silages made with LP1, and the aerobic stability of uninoculated ear and stover silages did not differ from silages made with LB. Stover silages made with LP2 and ensiled for 35 d had a lower proportion of lactic acid in total fermentation products compared with LP1. The aerobic stability and dry matter recovery of ear and stover silages in this study were not improved when made with LB, LP1, or LP2, due to the indigenous highly heterolactic fermentation that prevailed in the uninoculated ear and stover during 130-d ensilage.